Impact of NiO2 Nanoparticles and Curcumin on Testis Torsion/Detorsion Injury: Role of miR-34 and circRNA 0001518 : - Hashemi, Mehrdad; Zarei Moradi, Shabnam; Angaji, Seyed Abdolhamid; Salehi, Mitra (Galen Medical Journal, 2021)
Background: Testicular torsion is one cause of infertility without proper treatment. In this study, we investigate the effects of NiO2 nanoparticles (NPs) and curcumin on sperm parameters in rats and the expressions of genes involved in the apoptotic pathway, as well as expressions of miR-34 and circRNA 0001518. Materials and Methods: Forty-eight rats were randomly divided into eight groups: control (healthy rats), control rats that received NiO2-NPs, healthy rats that received curcumin, rats that received simultaneous NiO2-NPs and curcumin, untreated testicular ischemia/reperfusion (I/R) rats, testicular I/R rats that received NiO2-NPs, testicular I/R rats that received curcumin, and testicular I/R rats that received NiO2-NPs and curcumin. Then, sperms were extracted from the rats' epididymides to analyze concentration, viability, morphology, and motility. The cellular apoptosis level was studied using flow cytometry. Also, Bad and Bcl-X gene expressions and miR-34 and circRNA 0001518 levels were measured. Results: We observed improved sperm parameters in the testicular I/R) rats that received curcumin and NiO2-NPs. Administration of NiO2-NPs to healthy rats increased both apoptosis and the Bad/Bcl-X expression ratio. However, its administration to testicular I/R rats alone or with curcumin decreased apoptosis and the Bad/Bcl-X expression ratio and increased expressions of miR-34 and circRNA 0001518. Conclusion: Administration of NiO2-NPs and curcumin, alone or in combination, can have therapeutic effects in testicular I/R conditions by altering the expressions of genes in the mitochondrial apoptotic pathway and their regulatory elements. [GMJ.2021;10:e2342]